The Planning Concept of Wat Borom Phuttharam in Urban Context - Sheewasukthaworn, Wiroj (NAJUA: History of Architecture and Thai Architecture, 2020)
The paper presents the concept of Wat Borom Phuttharam's planning concerning the urban context, explores both in physical and political aspects. The results reveal that Wat Borom Phuttharam's layout is different from the traditional layout. Lying along the north-south axis, which is parallel to the street and canal, Wat Borom Phuttharam's layout was created in relation to essential places in the centre of Phra Nakhon Si Ayutthaya, such as Wat Phra Sri Sanphet and Phra Thinang Chakrawad Paichayon Mahaprasat. Besides, the construction of Wat Borom Phuttharam suggests the relationship between King Prasat Thong and King Phra Phetracha evidencing in donating their former estate before ascending the throne for building a monastery as well as in upholding Buddhism like the Chakravartin.